Menentukan Kebutuhan Material Penyemenan Plug Pada Trayek 26” Lapangan “PAS” Sumur “ASY” - Aly Rasyid; M. Mahlil Nasution; Phillip Asy Syams (Jurnal Bhara Petro Energi, 2024)
Drilling operations are one of the most vital operations in supporting the oil and gas production efforts of a field. Cement plug or plugging is a term used in the oil and gas industry to refer to the process of cement well plugs in drilling wells that have various purposes, these cement plugs can be installed at various depths in the well. This research was conducted with several methodologies from the type of research, data collection techniques, data analysis, and data processing. In the process of cementing the 26 "route plug, the volume capacity of cement slurry obtained is 150.27 bbls, the total required sack of cement is 746.63 sacks, the acquisition of mix water required in the 26" route plug cementing process required is 83.16 bbls, the additives needed for this cementing for tail slurry are silica flour of 28073.29 lb, Antifoam Agent 7.46 gal, Dispersant 140.37 lb, and Accelerator of 210.55 lb. In calculating cementing materials, detailed accuracy is needed, because if there is an error in the calculation, it will cause a fatal failure, and the development of technology today can facilitate the determination of cementing material requirements, including automatic calculation software, more effective cementing materials and control systems for monitoring in real time.